Keabsahan Akta Notaris Memuat Klausula Nominee dalam Transaksi Peralihan Hak Atas Tanah Untuk Kepemilikan Tanah Orang Asing: Studi Putusan Nomor (259/PDT.G/2020/PN.GIN) - Pramita, Helen; Rasji, Rasji (UNES Law Review, 2023)
The nominee agreement involves David John Lock and Ann Lilian Lock (Plaintiffs I and II) from Australia with Anak Agung Gede Oka Yuliartha (Defendant) concerning the transfer of funds amounting to AUD 860,000 for the purchase of land and the construction of Villa Puncak Bukit in Bali. Notary Anak Agung Bagus Putrajaya is involved in the creation of the nominee agreement deed. This study focuses on the notary's accountability in addressing challenges in the practice of nominee name lending by evaluating the notary's role as a property transaction supervisor and a public official who creates nominee deeds. The ownership of land by foreigners, often resulting in the practice of nominee agreements to circumvent restrictions on land ownership by foreigners. The notary, as a party involved in the deed creation, bears responsibility in civil, criminal, and administrative aspects. Errors in the nominee agreement can lead to its cancellation and legal consequences. Therefore, the notary needs to be cautious and ensure that every agreement made complies with applicable legal requirements, especially those related to legitimate objects and causes. In the context of the relationship between parties, the nominee agreement demonstrates a reciprocal nature between the involved parties, with the fulfillment of obligations as a performance. However, the characteristics of lastgeving indicate the dominance of the grantor, which can impact the enforceability of the agreement.